Application of Airborne Infrared Remote Sensing to the Study of Ocean Submesoscale Eddies - Marmorino, George O.; Smith, Geoffrey B.; North, Ryan P.; Baschek, Burkard (Frontiers in Mechanical Engineering, 2018)
This paper explores the use of infrared remote sensing methods to examine submesoscale eddies that recur downstream of a deep-water island (Santa Catalina, CA). Data were collected using a mid-wave infrared camera deployed on an aircraft flown at an altitude of 3.7 km, and research boats made nearly simultaneous measurements of temperature and current profiles. Structure within the thermal field is generally adequate as a tracer of surface fluid motions, though the imagery needs to be processed in a novel way to preserve the smallest-scale tracer patterns. In the case we focus on, the eddy is found to have a thermal signature of about 1 km in diameter and a cyclonic swirling flow. Vorticity is concentrated over a smaller area of about 0.5 km in diameter. The Rossby number is 27, indicating the importance of the centrifugal force in the dynamical balance of the eddy. By approximating the eddy as a Rankine vortex, an estimate of upward doming of the thermocline (about 14 m at the center) is obtained that agrees qualitatively with the in-water measurements. Analysis also shows an outward radial flow that creates areas of convergence (sinking flow) along the perimeter of the eddy. The imagery also reveals areas of localized vertical mixing within the eddy thermal perimeter, and an area of external azimuthal banding that likely arises from flow instability.